Pengaruh Good Corporate Governance (GCG) Dan Invesment Opportunity Set (IOS) Terhadap Nilai Perusahaan Konstruksi Pada PT Adhi Karya (Persero) Tbk Periode 2015-2024 - Diah Ayu Indah Lestari; Widya Intan Sari (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
Abstract. The aim of this research is to investigate the impact of Good Corporate Governance (GCG) and Investment Opportunity Set (IOS) on the value of construction companies at PT Adhi Karya (Persero) Tbk for the 2015-2024 period. The research method used is descriptive quantitative. In analyzing the data, the methods used include: Descriptive Statistics, Classical Assumption Tests (Normality, Multicollinearity, Heteroscedasticity, Autocorrelation), Multiple Linear Regression Tests, and Hypothesis Tests (t Test for partial testing and f Test for simultaneous testing), and Coefficient of Determination Test (R2). The findings in this research indicate that Good Corporate Governance does not have a significant influence on the Company Value of PT Adhi Karya (Persero) Tbk, this can be seen from the Tcount which is smaller than the Ttable 0.354 < 2.365. The significance value for GCG is 0.742 > 0.05. Meanwhile, the Investment Opportunity Set has a significant impact on the Company Value of PT Adhi Karya (Persero) Tbk, which can be seen from the Tcount which is greater than Table 12. 955 > 2. 365 and IOS significance value 0. 000 < 0. 05. Simultaneously, Good Corporate Governance and Investment Opportunity Set influence the Company Value of PT Adhi Karya (Persero) Tbk. This is proven by Fcount which is greater than Ftable 109.272 > 4.46 with a significance value of 0.000 < 0.05. The coefficient of determination shows a figure of 96.9%, while the remaining 3.1% is influenced by other variables not examined in this study.